2011
DOI: 10.1121/1.3587708
|View full text |Cite
|
Sign up to set email alerts
|

Overview of an indoor sonic boom simulator at NASA Langley Research Center.

Abstract: A facility has been constructed at NASA Langley Research Center to simulate the soundscape inside residential houses that are exposed to environmental noise from aircraft. This controllable indoor listening environment, the Interior Effects Room, enables systematic study of parameters that affect psychoacoustic response. The single-room facility, built using typical residential construction methods and materials, is surrounded on adjacent sides by two arrays of loudspeakers in close proximity to the exterior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…For validation purposes, the code predictions were compared with real measurements for four test structures subjected to simulated and real sonic booms . The accuracy of the predictions is shown here from results obtained in the National Aeronautics and Space Administration Interior Effects Room . This structure is an indoor listening environment to enable systematic study of parameters that affect psychoacoustic response to sonic booms.…”
Section: Vibro‐acoustic Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For validation purposes, the code predictions were compared with real measurements for four test structures subjected to simulated and real sonic booms . The accuracy of the predictions is shown here from results obtained in the National Aeronautics and Space Administration Interior Effects Room . This structure is an indoor listening environment to enable systematic study of parameters that affect psychoacoustic response to sonic booms.…”
Section: Vibro‐acoustic Prediction Modelmentioning
confidence: 99%
“…The arrays, containing 52 subwoofers and 52 midrange speakers, have a usable bandwidth of 3 to 5 kHz and sufficient power output to allow study of sonic boom noise. Specific details on the exact location of the loudspeaker arrays can be found in Klos et al . The vibration of the building components also induces nonlinear vibro‐acoustic responses due to rattle (intermittent loss of contact between two structural components), friction (relative motion of two components with rough surfaces) and so forth.…”
Section: Vibro‐acoustic Prediction Modelmentioning
confidence: 99%
“…Subjective testing in previous simulators, in homes, and in the field [8] have shown that human annoyance to sonic booms outdoors is best predicted by the loudness level metric Perceived Level (PL) [11,12]. Indications that human response may differ when experiencing sonic booms in an indoor environment [13] motivated construction of the Interior Effects Room (IER) at NASA Langley Research Center [6]. The unique capabilities of this facility include a realistic indoor soundscape within the context of a residential living room environment.…”
Section: Sonic Boom Subjective Test Facility Overviewmentioning
confidence: 99%
“…4. Note that the signals are labeled with the shock rise times (3,6, and 12 ms) corresponding to their respective exterior waveforms. The energy spectral density for the exterior and interior signals are given in Fig.…”
Section: Measurement Of Signals At Facility Exterior and Interiormentioning
confidence: 99%
See 1 more Smart Citation